2021
DOI: 10.26533/eksis.v16i1.773
|View full text |Cite
|
Sign up to set email alerts
|

Green Investment: Incorporate Environment, Social, And Government Factors In Investment Decision

Abstract: There are two types of investors, the first is the type of investor who focuses on return on investment and the second type is the investor who pays attention to Environmental, Social, and Governance (ESG) values in investing. This requires management to make adjustments to create a competitive advantage. One of the frameworks used to measure the competitive advantage of a company is the Porter framework. However, Porter's framework needs to be supplemented with ESG values to capture the value creation process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, the MCDM methods might have some limitations, such subjectivity, trade-offs and conflicting objectives, sensitivity to methodology, and lack of transparency [37]. Specifically, complexity is increased in cases where the data are more diversified and enlarged, which makes traditional MCDM methods difficult to apply in the big data era, and we know that green investment research is increasingly incorporating big data analysis [24]. For example, Wang et al found out that big data technology makes it feasible to analyze enormous and complex data sets, giving businesses the ability to identify business innovation opportunities and improve their environmentally friendly operations [38].…”
Section: Green Investment In the Big Data Eramentioning
confidence: 99%
See 1 more Smart Citation
“…However, the MCDM methods might have some limitations, such subjectivity, trade-offs and conflicting objectives, sensitivity to methodology, and lack of transparency [37]. Specifically, complexity is increased in cases where the data are more diversified and enlarged, which makes traditional MCDM methods difficult to apply in the big data era, and we know that green investment research is increasingly incorporating big data analysis [24]. For example, Wang et al found out that big data technology makes it feasible to analyze enormous and complex data sets, giving businesses the ability to identify business innovation opportunities and improve their environmentally friendly operations [38].…”
Section: Green Investment In the Big Data Eramentioning
confidence: 99%
“…Green investment research is increasingly incorporating big data analysis [24]. Big data is prone to the same types of biases as is data analysis utilizing different data sources since it neither modifies the nature of knowledge nor applies fundamentally novel techniques for extracting knowledge from the data.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al (2014) state that companies that have implemented ESG will produce better operational performance. Cakranegara and Sidjabat (2021) stated that companies implementing ESG will increase the company's competitive advantage, which will ultimately increase company value. Implementing ESG by existing regulations will increase the company's credibility.…”
Section: Coefficient Probability Coefficient Probability Coefficient ...mentioning
confidence: 99%
“…to increase the competitive advantage that produces favorable performance for companies and also shows two forms of returns from the financial and social sides from stakeholders, such as investors, to engage in investment (Cakranegara & Sidjabat, 2021;Paulakarin et al, 2020).…”
Section: Conversely Esg Aspects Have Been Demonstratedmentioning
confidence: 99%